Pressures on Boreal Riparian Vegetation: A Literature Review - Hoppenreijs, Jacqueline H. T.; Eckstein, R. Lutz; Lind, Lovisa (Frontiers in Ecology and Evolution, 2022)
Riparian zones are species-rich and functionally important ecotones that sustain physical, chemical and ecological balance of ecosystems. While scientific, governmental and public attention for riparian zones has increased over the past decades, knowledge on the effects of the majority of anthropogenic disturbances is still lacking. Given the increasing expansion and intensity of these disturbances, the need to understand simultaneously occurring pressures grows. We have conducted a literature review on the potential effects of anthropogenic pressures on boreal riparian zones and the main processes that shape their vegetation composition. We visualised the observed and potential consequences of flow regulation for hydropower generation, flow regulation through channelisation, the climate crisis, forestry, land use change and non-native species in a conceptual model. The model shows how these pressures change different aspects of the flow regime and plant habitats, and we describe how these changes affect the extent of the riparian zone and dispersal, germination, growth and competition of plants. Main consequences of the pressures we studied are the decrease of the extent of the riparian zone and a poorer state of the area that remains. This already results in a loss of riparian plant species and riparian functionality, and thus also threatens aquatic systems and the organisms that depend on them. We also found that the impact of a pressure does not linearly reflect its degree of ubiquity and the scale on which it operates. Hydropower and the climate crisis stand out as major threats to boreal riparian zones and will continue to be so if no appropriate measures are taken. Other pressures, such as forestry and different types of land uses, can have severe effects but have more local and regional consequences. Many pressures, such as non-native species and the climate crisis, interact with each other and can limit or, more often, amplify each other’s effects. However, we found that there are very few studies that describe the effects of simultaneously occurring and, thus, potentially interacting pressures. While our model shows where they may interact, the extent of the interactions thus remains largely unknown.